ROARING INTO FREEDOM: FEMINIST CONSCIOUSNESS AND THE RECLAMANTION OF VOICE IN ABI DARES’S AND SO I ROAR - Muhammad, Putroe Kamaliah; Purwarno, Purwarno (Universitas Muhammadiyah Lampung, 2026)
This study addresses the limited scholarly attention to how feminist consciousness is narratively constructed through voice reclamation in contemporary African fiction, particularly within the intersecting forces of patriarchy and postcoloniality. Existing studies largely foreground themes of oppression but often neglect the linguistic and narrative mechanisms through which marginalized women negotiate and rearticulate agency. Focusing on And So I Roar by Abi Daré, this study examines how the protagonist reclaims her voice as a form of resistance within constraining socio-cultural structures. The study aims to analyze how narrative voice, agency, and self-representation function as strategies that move the protagonist from enforced silence to empowered speech. Employing a qualitative descriptive approach, the research applies feminist textual analysis and close reading to identify narrative strategies, linguistic patterns, and symbolic acts. The analysis is informed by feminist literary criticism, subaltern feminist theory, and feminist linguistics. The findings reveal three key patterns: (1) narrative voice as resistance to patriarchal silencing, (2) agency expressed through storytelling and linguistic self-assertion, and (3) the transformation of personal speech into a collective political voice. These strategies position voice reclamation as both personal empowerment and a critique of patriarchal and colonial marginalization, contributing to African feminist literary scholarship and advancing discourse on gender justice.